Preliminary study on pre-treatment physical activity and quality of life in infertility - Viktória Prémusz; Alexandra Maka; Boróka Gács; Ágnes Nagy; Beatrix Perjés; Pongrác Ács; Kinga Lampek; Ákos Várnagy (University of Novi Sad, Faculty of Sport and Physical Education, 2019)
The increasing incidence of infertility and contrary the remaining levels of success rate of assisted reproductive therapies (ART) justify expanding the biomedical approach and underline the importance of psychosocial and lifestyle factors. The aim of the study was to examine the effects of pre-treatment physical activity (PA) on the quality of life (QoL) in infertile women. A cross sectional cohort study was carried out involving 50 female patients with infertility diagnosis. Standardized QoL questionnaires and pre-treatment PA patterns were administrated during December 2018 - April 2019 in a university hospital-based fertility centre in South-Hungary. 43% of the women reported regular exercise. Regarding GPAQ moderate intensity PA in work and recreation was preferred. They spent 4,2 hours with active transportation weekly, and 4.5 hours sedentary daily. 68,89% reached the 150min/week MVPA recommendation and 18,2% spent more than 4 hours with exercise Respondents were less satisfied with Physical Domain (57.7±7.5) and most with Psychological Domain (72.2±12.1) of WHOQOL-BREF. Lower QoL by Emotional (56.46±18.12) and Mind-Body (56.84±19.67), mediate by Social (62.76±17.40) and better values by Relational Subscale (76.48±19.62) were measured with FertiQoL. Significant difference between active and inactive group was described for Psychological domain (Z=-2.240, p=0.025). Positive correlation was found between MVPA vs Total MET and Emotional Subscale (p=0.014, p=0.009) and between work-related PA and Mind-body Subscale (p=0.006). Pre-treatment PA could positively affect QoL undergoing ART. However, for more impressive results, objective assessment of physical activity, increased number of participants, and further examinations are needed.